Being the monster: women's narratives of body and self after treatment for breast cancer. Issue 1 (26th May 2006) - Rosenblatt, L
Abstract : Serious illness and its treatment frequently changes a woman's sense of herself and her body. Narrative medicine posits that individuals permitted to tell their stories regain control over the plotline of the illness, reclaim the central role as protagonist, and thus diminish the sense of helplessness, marginalisation, and isolation that are inevitable aspects of serious disease. The women presented here speak about losses that occur during treatment for advanced cancer. These losses include: loss of the former body; loss of one or both breasts; loss of hair; loss of fertility, and changes in weight, energy, and sexuality. This paper will not review the medical literature on the psychological aspects of change in appearance secondary to disease and/or treatment. As a way of broadening our understanding of what women attempt to communicate to their care providers about who they are and who they are becoming through the experience of illness, this paper will present brief excerpts from the interviews of four women talking about issues of identity and bodily change, using concepts of feminine identity developed by the French psychoanalytic theorist Hélène Cixous in her essay, The laugh of the Medusa.